PENDIDIKAN AKHLAK DALAM PENINGKATAN KUALITAS IBADAH (PENDEKATAN TASAWUF AMALI) - Hasibuan, Armyn (IAIN Padangsidimpuan, 2014)
Education is the soul of Islami. Education directed the formation of a noble character towards the creation of a more perfect human condition has duties as divine servants, civil servants and assumed the title of caliph of God on this earth. Allah says that the creation of man is for the man in the broad sense to Allah. Most of it is devoted to worship either vertically or horizontally.Even in the study of Sufism amali, worship Allah is the second character to him after his faith. Human existence must see worship something that should be part of his existence he had prepared, he learned, he improved and increased in quality and quantity. Because he had to make himself the servant before him submissive and obedientSufism amali loaded with guidance and direction, sothat each person can make various Muslim believers’ life is worth worship activities. Every motion and breathing is solely because of his good deeds multiply coupled with sincere for Allah. Likewise signaling in liver disease resulting lazy people worship